Methylome analysis for spina bifida shows SOX18 hypomethylation as a risk factor with evidence for a complex (epi)genetic interplay to affect neural tube development. Issue 1 (December 2016) - Rochtus, Anne; Winand, Raf; Laenen, Griet; Vangeel, Elise; Izzi, Benedetta; Wittevrongel, Christine; Moreau, Yves; Verpoorten, Carla; Jansen, Katrien; Van Geet, Chris; Freson, Kathleen
Abstract Background Neural tube defects (NTDs) are severe congenital malformations that arise from failure of neurulation during early embryonic development. The molecular basis underlying most human NTDs still remains largely unknown. Based on the hypothesis that folic acid prevents NTDs by stimulating methylation reactions, DNA methylation changes could play a role in NTDs. We performed a methylome analysis for patients with myelomeningocele (MMC). Using a candidate CpG analysis forHOX genes, a significant association betweenHOXB7 hypomethylation and MMC was found. Methods In the current study, we analyzed leukocyte methylome data of ten patients with MMC and six controls using Illumina Methylation Analyzer and WateRmelon R-packages and performed validation studies using larger MMC and control cohorts with Sequenom EpiTYPER. Results The methylome analysis showed 75 CpGs in 45 genes that are significantly differentially methylated in MMC patients. CpG-specific methylation differences were next replicated for the top six candidate genesABAT, CNTNAP1, SLC1A6, SNED1, SOX18, andTEPP but only for theSOX18 locus a significant overall hypomethylation was observed (P value = 0.0003). Chemically induced DNA demethylation in HEK cells resulted inSOX18 hypomethylation and increased expression. Injection ofsox18 mRNA in zebrafish resulted in abnormal neural tube formation. Quantification of DNA methylation for theSOX18 locus was also determined for five families where parents had normal methylation values compared to significant lower values for both the MMC as their non-affected child.SOX18 methylation studies were performed for a MMC patient with a paternally inherited chromosomal deletion that includesBMP4 . The patient showed extremeSOX18 hypomethylation similar to his healthy mother while his father had normal methylation values. Conclusions This is the first genome-wide methylation study in leukocytes for patients with NTDs. We reportSOX18 as a novel MMC risk gene but our findings also suggest thatSOX18 hypomethylation must interplay with environmental and (epi)genetic factors to cause NTDs. Further studies are needed that combine methylome data with next-generation sequencing approaches to unravel NTD etiology.